2000
DOI: 10.1136/thorax.55.5.388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of pulmonary Mycobacterium avium complex infection in human T lymphotrophic virus type I carriers

Abstract: Background-Little is known about pulmonary Mycobacterium avium complex (MAC) infection in human T lymphotrophic virus type I (HTLV-I) carriers. A study was undertaken to investigate and clarify the characteristics of pulmonary MAC infection in these subjects. Methods-Twenty nine patients with pulmonary MAC infection without any underlying pulmonary disorder were investigated. The clinical features and radiographic appearance of HTLV-I carriers and non-carriers were compared and the bronchoalveolar lavage (BAL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…35 These findings are considered as evidence of immunodeficiency in HTLV-I-infected individuals, which is due to suppression of naive T lymphocytes. Recent studies by Matsuyama and colleagues 36 have demonstrated high seropositivity among patients with Mycobacterium avium complex (MAC) infection. Because defense against MAC infection depends on cell-mediated immunity, especially T lymphocytes, impaired cellmediated immunity in HTLV-I carriers might be responsible for increased susceptibility to MAC infection.…”
Section: Discussionmentioning
confidence: 99%
“…35 These findings are considered as evidence of immunodeficiency in HTLV-I-infected individuals, which is due to suppression of naive T lymphocytes. Recent studies by Matsuyama and colleagues 36 have demonstrated high seropositivity among patients with Mycobacterium avium complex (MAC) infection. Because defense against MAC infection depends on cell-mediated immunity, especially T lymphocytes, impaired cellmediated immunity in HTLV-I carriers might be responsible for increased susceptibility to MAC infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, some subtle immune defects are apparent even in the otherwise healthy HTLV-1 infected population. Compared to individuals without HTLV-1 infection, parasite load is higher and chronic carriage more common in subjects with strongyloidiasis and HTLV-1 co-infection (reviewed in13), Mycobacterium avium complex infection causes more extensive pulmonary lesions in HTLV-1 infected subjects,14 and HTLV-1 infected subjects are at increased risk for bladder or kidney infections, possibly related to neurological dysfunction 15,16. A detailed understanding of the immuno-pathophysiology underlying HTLV-1 disease associations is lacking, in part because many studies have been narrowly focused.…”
Section: Introductionmentioning
confidence: 99%
“…5 HTLV-I infection affects not only the peripheral blood lymphocytes but also the lymphocytes in the lungs 1314 Taken together, we think that the enhanced inhibitory effect of MAC GPL observed in this in vitro study is one of the reasons why MAC spreads more widely in lungs of individuals infected with HTLV-I 2. It may be necessary to treat pulmonary MAC infection in HTLV-I carriers even if there are no immunological abnormalities in the clinical data.…”
Section: Discussionmentioning
confidence: 71%
“…Blood samples were obtained from 29 individuals who had recovered from pulmonary MAC infection, 10 of whom also had HTLV-I (all women, mean (SD) age 70.1 (10.2) years) and 19 who did not have HTLV-I (16 women, mean (SD) age 70.9 (9.5) years) 2. They had neither systemic nor local underlying disorders which might predispose to pulmonary MAC infection such as alcoholism and residual pulmonary damage from previous infection, nor any unexplained pulmonary diseases or other pathogens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation